Empowering smallholder farmers by sustainable fodder development for improved animal management in Odisha - Das, Swetasmita (Heifer International, 2023)
Smallholder women farmers in the eastern Indian state of Odisha play a crucial role in the management of goat and backyard poultry. However, they face significant challenges due to fodder shortages, which adversely affect their livelihoods. This abstract highlights the efforts of Heifer International in addressing the fodder scarcity through sustainable farming practices, with a particular focus on smallholder women farmers in Odisha. Heifer International’s project in Odisha aims to promote the cultivation of diverse fodder crops, including tree fodders like moringa and subabul, grasses like napier and blue buffel, and seasonal crops like maize and cowpea. The project places a strong emphasis on the adoption of sustainable farming practices and provides targeted training to members of self-help groups (SHGs) on improved animal management and good agricultural practices (GAP) for fodder development. This training equips women farmers with the necessary knowledge and skills to cultivate fodder sustainably, considering factors such as land type, size, irrigation facilities, and the selection of high-quality planting materials. By addressing the challenges of fodder scarcity, Heifer International’s project in Odisha contributes to the economic development and empowerment of smallholder women farmers. Access to nutritious and sustainable animal feed sources throughout the year enhances the health and productivity of their livestock, particularly, goat and backyard poultry, thereby improving their overall livelihoods. Furthermore, by actively involving women in decision-making processes and income-generating activities related to livestock farming, the project promotes gender equality and women’s empowerment within the tribal communities of Odisha.